Osmolyte accumulation regulates the SUMOylation and inclusion dynamics of the prionogenic Cyc8-Tup1 transcription corepressor - Nadel, Cory M. (PLoS Genet, 2019)
Environmental stressors can severely perturb cellular homeostasis and compromise viability. To cope with environmental stressors, eukaryotes have developed distinct signaling programs that allow for adaptation during different stress conditions. These programs often require a host of post-translational modifications that alter proteins to elicit appropriate cellular responses. One crucial protein modifier during stress is the small ubiquitin-like modifier SUMO. In many cases, however, the functions of stress dependent protein SUMOylation remain unclear. Previously, we showed that the conserved Saccharomyces cerevisiae Cyc8-Tup1 transcriptional corepressor complex undergoes transient hyperosmotic stress-induced SUMOylation and inclusion formation, which are important for appropriate regulation of hyperosmotic-stress genes. Here, we show the osmostress-responsive MAP kinase Hog1 regulates Cyc8 SUMOylation and inclusion formation via its role in the transcriptional activation of glycerol biosynthesis genes. Mutations that ablate Cyc8 SUMOylation can partially rescue the osmosensitivity of hog1Δ cells, and this is facilitated by inappropriate derepression of glycerol-biosynthesis genes. Furthermore, cells specifically unable to synthesize the osmolyte glycerol cause transient Cyc8 SUMOylation and inclusions to persist, indicating a regulatory role for glycerol to reestablish the basal state of Cyc8 following adaptation to hyperosmotic stress. These observations unveil a novel intersection between phosphorylation and SUMOylation networks, which are critical for shifting gene expression and metabolic programs during stress adaptation.